Australian Labor as a Federal Organisation: State Uniformity or Distinctiveness?. (21st April 2020) - Gauja, Anika; Grömping, Max
Abstract : Is the Australian Labor Party (ALP) one party, or eight? Academic accounts of the ALP throughout its history have emphasised the importance of state‐based policy‐making and organisation as evidence that the "life of the party" occurs within state and territory branches. However, over the last three decades, changes to the national conference and constitution, the increasing prominence of national leaders and the professionalisation of campaigning practices have arguably created the conditions for a far more centralised organisation, raising the question of whether, in 2019, there is anything distinctive about the ALP state and territory branches beyond the jurisdictions in which they operate. In this article, we investigate the distinctiveness of state Labor branches in terms of their formal organisational diversity and the characteristics and attitudes of their supporters. Using data from an original survey of Australian party supporters conducted in 2016, as well as undertaking an analysis of formal party rules, we show that the ALP exhibits a high degree of organisational uniformity across its branches, and supporters of the party in all states and territories very closely resemble each other. We conclude that even though the party maintains a federal structure it is possible to study its supportership and formal structure as a national organisation.